(untitled) (Journal of Current and Advance Medical Research, 2016)
Background: Atrial septal defect (ASD) is one of the important congenital anomaly. Objective: The present study is designed to determine how the different morphological types of ASD are distributed among Bangladeshi Bengali patients undergoing surgical repair and to see the clinical features of the above patients. Methodology: This cross-sectional descriptive study was carried out on the 50 ASD patients undergoing surgical repair at the National Institute of Cardiovascular Diseases (NICVD) or the National Heart Foundation and Research Institute (NHF & RI) in Dhaka, during the period of July 2010 to June 2011 to explore different morphological types and clinical presentation. The morphological types of ASD were revealed by echocardiography and confirmed preoperatively. Result: A total number of 50 patients were recruited in this study of which ostium secundum type was found in 96% cases and sinus venosus type in 4% cases. Evaluation of patients showed that 14% of the patients were asymptomatic and they were detected incidentally. The most common symptoms were palpitation, dyspnea, recurrent RTI, fatigue, failure to thrive and chest pain. The commonest signs at diagnosis included loud S1, wide and fixed splitting S2, systolic murmur, tachycardia, shifting of the apex beat and left parasternal lift. Surgical closure has been the mainstream of treatment. Conclusion: In conclusion ostium secundum is the most common type of ASD.